2018
DOI: 10.1155/2018/7959815
|View full text |Cite
|
Sign up to set email alerts
|

Improving Traffic State Prediction Model for Variable Speed Limit Control by Introducing Stochastic Supply and Demand

Abstract: Variable speed limit (VSL) is becoming recognized as an effective way to improve traffic throughput and road safety. In particular, methods based on traffic state prediction exhibit promising potential to prevent future traffic congestion and collisions. However, field observations indicate that the traffic state prediction model results in nonnegligible error that impacts the next step decision making of VSL. Thus, this paper investigates how to eliminate this prediction error within a VSL environment. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Bie et al [19] developed a variation of the METANET model by integrating it with the Stochastic Cell Transmission Model (SCTM) for traffic prediction. A different objective function was determined in [20], whose formulation linked accident risk with the adoption of VSLs.…”
Section: State Of Artmentioning
confidence: 99%
“…Bie et al [19] developed a variation of the METANET model by integrating it with the Stochastic Cell Transmission Model (SCTM) for traffic prediction. A different objective function was determined in [20], whose formulation linked accident risk with the adoption of VSLs.…”
Section: State Of Artmentioning
confidence: 99%
“…However, MPC approach was widely used to ramp metering and speed guidance [9][10][11][12][13]. Moreover, dynamic speed limit control was jointly applied with other models, such as a traffic state prediction model [14][15][16]. From the literature review, it was found that the operational efficiency or capacity was used as the main optimization objective while traffic safety was rarely considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e volume equation for the on-ramp is shown in equations (13) and (14), where q i (ρ jam − ρ i (k))/(ρ jam − ρ cr ) indicates the merging volume to mainline and d i (k) + w i (k)/T indicates the on-ramp demand. Meanwhile, the final merging volume will also be subject to the on-ramp metering rate, r i (k).…”
Section: On-ramp Flow Equationmentioning
confidence: 99%
“…Kotsialos et al [11] used the second-order traffic flow METANET model as a core model, which had good expression characteristics for VSL control. ese experiment results showed that advanced models can effectively improve the traffic capacity of road congested sections, including SCTM-METANET [12], proactive VSL based on Dyna TAM-VSL [13], a variety of vehicles model [14], and predictive control based on the cell transmission model [15].…”
Section: Introductionmentioning
confidence: 99%